Daerah Penangkapan Potensial Tuna Madidihang Thunnus albacares, Bonnaterre, 1788 (Teleostei:Scombridae) di Laut Seram - Jacobus Bunga Paillin; Delly Dominggas Paulina Matrutty; Stany Rachel Siahainenia; Ruslan Husen Saban Tawari; Haruna Haruna; Putri Talahatu (Jurnal Kelautan Tropis, 2020)
This research aims are to determine the potential fishing grounds of yellowfin tuna based on the approach of sea surface temperature, chlorophyll-a and catches in the Ceram Sea. Overall catches of 407 Individuals. In January the total catches were 66 individuals (14.44%), in February 67 individuals (14.66%), in March 84 individuals (18.38%), in April 116 individuals (25.38%) and in May 124 individuals (27.13%). The distribution of sea surface temperature and chlorophyll-a in the Ceram Sea in January-May 2019 looks varied. In January the average sea surface temperature was 29.13 oC, in February sea surface temperature was 29.54 oC, in March sea surface temperature was 30.12 oC, in April sea surface temperature was 30.12 oC, in May sea surface temperature was 29.77 oC. Chlorophyll-a concentration in January and February was 0.21 mg/m3, March was 0.20 mg/m3, April was 0.16 mg/m3, and May was 0.25 mg/m3. The results of the t-test analysis showed the P-value of sea surface temperature was 0.009<0.05, chlorophyll-a P-value 0.00048<0.05. Determination of potential fishing areas based on sea surface temperature, chlorophyll-a, and CPUE indicators shows that potential fishing areas are found in January, February, March, and May, while in April are in the medium potential category. Penelitian ini dilaksanakan dengan tujuan menentukan daerah penangkapan potensial Tuna madidihang berdasarkan pendekatan suhu permukaan laut, klorofil-a dan hasil tangkapan di Laut Seram.  Secara keseluruhan hasil tangkapan ikan tuna madidihang sebanyak 407 Individu. Bulan Januari total hasil tangkapan sebanyak 66 individu (14.44%), bulan Februari 67 individu (14.66%), bulan Maret 84 individu (18.38%), bulan April 116 individu (25.38%) dan bulan Mei 124 individu (27.13%). Sebaran suhu permukaan laut dan klorofil-a di Laut Seram pada bulan Januari-Mei 2019 terlihat bervariasi. Bulan Januari rata-rata suhu permukaan laut sebesar 29.13 oC, bulan Februari suhu permukaan laut 29.54 o, bulan Maret suhu permukaan laut 30.12 oC, bulan April suhu permukaan laut 30.12 oC, bulan Mei suhu permukaan laut 29.77 oC. Konsentrasi klorofil-a pada bulan Januari dan Februari sebesar 0.21 mg/m3, bulan Maret sebesar 0.20 mg/m3, bulan April sebesar 0.16 mg/m3, dan bulan Mei sebesar 0.25 mg/m3.  Hasil analisis uji t menunjukan nilai P-value suhu permukaan laut sebesar 0,009<0,05, klorofil-a P-value 0,00048<0,05. Penentuan daerah penangkapan ikan potensial berdasarkan indikator suhu permukaan laut, klorofil-a dan CPUE menunjukkan daerah penangkapan ikan potensial terdapat pada bulan Januari, Februari, Maret, dan Mei, sedangkan pada bulan April berada dalam kategori potensial sedang.